A Clinically Integrated mHealth App and Practice Model for Collecting Patient-Reported Outcomes between Visits for Asthma Patients: Implementation and Feasibility - Rudin, Robert S.; Fanta, Christopher H.; Qureshi, Nabeel; Duffy, Erin; Edelen, Maria O.; Dalal, Anuj K.; Bates, David W. (Applied Clinical Informatics, 2019)
Objective Mobile health (mHealth) apps may prove to be useful tools for supporting chronic disease management. We assessed the feasibility of implementing a clinically integrated mHealth app and practice model to facilitate between-visit asthma symptom monitoring as per guidelines and with the help of patient-reported outcomes (PRO).Methods We implemented the intervention at two pulmonary clinics and conducted a mixed-methods analysis of app usage data and semi-structured interview of patients and clinician participants over a 25-week study period.Results Five physicians, 1 physician's assistant, 1 nurse, and 26 patients participated. Twenty-four patients (92%) were still participating in the intervention at the end of the 25-week study period. On average, each patient participant completed 21 of 25 questionnaires (84% completion rate). Weekly completion rates were higher for participants who were female (88 vs. 73%, p = 0.02) and obtained a bachelor's degree level or higher (94 vs. 74%, p = 0.04). On average, of all questionnaires, including both completed and not completed (25 weekly questionnaires times 26 patient participants), 25% had results severe enough to qualify for a callback from a nurse; however, patients declined this option in roughly half of the cases in which they were offered the option. We identified 6 key themes from an analysis of 21 patients and 5 clinician interviews. From the patient's perspective, these include more awareness of asthma, more connected with provider, and app simplicity. From the clinician's perspective, these include minimal additional work required, facilitating triage, and informing conversations during visits.Conclusion Implementation of a clinically integrated mHealth app and practice model can achieve high patient retention and adherence to guideline-recommended asthma symptom monitoring, while minimally burdening clinicians. The intervention has the potential for scaling to primary care and reducing utilization of urgent and emergency care.
Keywords: mHealth; patient-reported outcomes; asthma; telehealth; feasibility study